2014
DOI: 10.1186/1472-6823-14-43
|View full text |Cite
|
Sign up to set email alerts
|

Testicular histological and immunohistochemical aspects in a post-pubertal patient with 5 alpha-reductase type 2 deficiency: case report and review of the literature in a perspective of evaluation of potential fertility of these patients

Abstract: BackgroundTesticular morphology and immunohistochemical studies have never been reported in genetically documented adult patients with 5 alpha-reductase type 2 deficiency (5α-R2 deficiency).Case presentationWe describe the testicular histopathology of a 17-year-old XY subject with 5α-R2 deficiency caused by the recurrent homozygous Gly115Asp loss of function mutation of the SRD5A2 gene.We also performed an immunohistochemical analysis in order to further study the relationship between seminiferous tubules stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Case Report M-A Burckhardt and others Histology of HSD3B2 deficiency 173:5 K8 Table 4 (8,9,12,13,14,16,23,24,25,26,27,28,29,30,31,32,33,34,35,36). For spermatogenesis and thus fertility, the few data available suggest that it varies between different androgen biosynthetic defects as well as between individuals carrying defects in the same gene.…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…Case Report M-A Burckhardt and others Histology of HSD3B2 deficiency 173:5 K8 Table 4 (8,9,12,13,14,16,23,24,25,26,27,28,29,30,31,32,33,34,35,36). For spermatogenesis and thus fertility, the few data available suggest that it varies between different androgen biosynthetic defects as well as between individuals carrying defects in the same gene.…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…21,54,55,57 AMH is absent in normal adult testes but can be reexpressed in pathological conditions such as testicular atrophy, androgen insensitive syndromes, 5α-reductase type 2 deficiency, and SC tumors. 20,27,58 As far as the rabbit species is concerned, previous studies have demonstrated the immunohistochemical expression of AMH in fetal testes. 26,55 In the present study, AMH was detected in neonatal and prepubertal testes, its expression decreased with age, and it was totally absent in adult testes.…”
Section: Discussionmentioning
confidence: 99%
“…Because intratesticular androgen concentration and androgen receptor expression are normal and FSH is not elevated, serum AMH is not increased in these patients [Stuchi-Perez et al, 2005;Vija et al, 2014].…”
Section: Defects Of Androgen Synthesismentioning
confidence: 99%